Staged Approach to Autologous Reconstruction in the Ptotic Breast: A Comparative Study. Issue 3 (May 2021) - Deptula, Peter; Yesantharao, Pooja; Wapnir, Irene; Nguyen, Dung
Abstract : Background: Nipple-sparing mastectomy (NSM) and autologous breast reconstruction are associated with higher patient satisfaction, quality of life, and aesthetic outcome. For patients with naturally ptotic breasts, this ideal reconstructive treatment of NSM and autologous breast reconstruction poses a challenge. We describe our experience in treating patients with ptotic natural breasts using a 2-staged approach: oncoplastic breast reduction in the first stage followed by nipple-sparing mastectomy and immediate autologous reconstruction in a second stage. Methods: We reviewed cases of patients with grade III ptosis who underwent a staged reconstruction approach with reduction mammaplasty followed by NSM and immediate reconstruction with an abdominally based free flap (2014–2019). We compared this group of patients to a second group who underwent staging with a technique of nipple-areola complex (NAC) devascularization. A survey was administered to assess for patient satisfaction and aesthetic outcome 1 year after the second stage procedure. Results: Eight patients were identified in our reduction group, and 9 patients were identified in our devascularization group. No cases of total NAC necrosis were noted in either group (0%). Two cases of partial NAC necrosis were noted in the devascularization group (11%), whereas none were observed in the reduction group. All patients were satisfied with final outcome (100%, P = 1.0). Aesthetic scores across all factors were higher in the reduction group. Scores for overall outcome (4.6 vs 3.7, P = 0.04), natural appearance (4.8 vs 3.8, P = 0.01), breast contour (4.8 vs 3.2, P = 0.002), and position of breasts (5.0 vs 3.9, P = 0.03) were significantly higher in the reduction group. Conclusions: Breast ptosis no longer represents a contraindication for patients desiring nipple-sparing mastectomy and immediate autologous reconstruction. This series supports the use of a 2-staged approach with reduction mammaplasty in patients with naturally ptotic breasts. A staged reduction approach may offer fewer NAC complications while also allowing for superior aesthetic outcomes.